Pleural fluid biomarkers to predict response to pleurodesis or indwelling pleural catheter for malignant pleural effusion: still a long way to go - Katrine Fjaellegaard; Sina Ahmadzai; José M. Porcel; Federico Mei; Jane A. Shaw; Uffe Bodtger (Respiratory Research)
Abstract This letter summarizes the current literature on pleural fluid biomarkers that predict treatment response to chemical pleurodesis and indwelling pleural catheters in patients with malignant pleural effusion. We found evidence on pleural fluid biomarkers to be limited to a few small studies, where the biomarkers prognostic value was not tested in separate validation cohorts. Although low pleural fluid LDH, high glucose, and high pH levels are associated with pleurodesis success, no clinically valuable biomarker has been identified. Hence, further research on the inflammatory processes of malignant pleural effusion and during definitive pleural procedures is needed, as well as proper testing of potential biomarkers in separate model derivation and validation cohorts.